Theoretical assessment of a highly sensitive photonic crystal fibre based on surface plasmon resonance sensor operating in the near-infrared wavelength. Issue 1 (2nd January 2019) - Liu, Chao; Su, Weiquan; Wang, Famei; Li, Xianli; Yang, Lin; Sun, Tao; Mu, Haiwei; Chu, Paul K.
ABSTRACT: A surface plasmon resonance (SPR) sensor comprising a photonic crystal fibre (PCF) with an annular analyte channel outside the fibre is described and analysed. The losses of the sensor are analysed by the finite element method (FEM) with the boundary condition of a perfectly matched layer (PML). The influence of the structural parameters on the performance of the sensor is investigated based on the loss spectra of the fundamental mode. The relationship between the resonance wavelengths and analyte refractive indexes is established for refractive indexes ranging from 1.395 to 1.425. An average spectral sensitivity of 12, 592.86 nm/RIU can be achieved in the sensing range corresponding to a resolution of 7.94×10 −6 RIU. The maximum spectral sensitivity and the maximum figure of merit (FOM) are as high as 22, 807.14 nm/RIU and 595.78, respectively.